Placebo and Nocebo Effects Across Symptoms: From Pain to Fatigue, Dyspnea, Nausea, and Itch - Wolters, Fabian; Peerdeman, Kaya J.; Evers, Andrea W.M. (Frontiers in Psychiatry, 2019)
Placebo and nocebo effects are, respectively, the helpful and harmful treatment effects that do not arise from active treatment components. These effects have thus far been researched most often in pain. It is not yet clear to what extent these findings from pain can be generalized to other somatic symptoms. This review investigates placebo and nocebo effects in four other highly prevalent symptoms: dyspnea, fatigue, nausea and itch. The role of learning mechanisms (verbal suggestions, conditioning) in placebo and nocebo effects on various outcomes (self-reported, behavioral, and physiological) of these different somatic symptoms is explored. A search of experimental studies indicated that, as in pain, the combination of verbal suggestion and conditioning is generally more effective than suggestion alone for evoking placebo and nocebo effects. However, conditioning appears more and verbal suggestions less relevant in symptoms other than pain, with the exception of placebo effects on fatigue and nocebo effects on itch. Physiological measures, such as heart rate, lung function, or gastric activity are rarely affected even when self-reported symptoms are. Neurobiological correlates are rarely investigated, and few commonalities appear across symptoms. Expectations generally predict placebo and nocebo effects for dyspnea and itch but seem less involved in fatigue and nausea. Individual characteristics do not consistently predict placebo or nocebo effects across symptoms or studies. In sum, many conclusions deriving from placebo and nocebo pain studies do appear to apply to other somatic symptoms, but a number of important differences exist. Understanding what type of learning mechanisms for which symptom are most likely to trigger placebo and nocebo effects is crucial for generalizing knowledge for research and therapies across symptoms and can help clinicians to optimize placebo effects in practice.